Sarmatian Treasures Reconsidered. Some Remarks on the New Book by Leo Klein - Mordvintseva, Valentina I. (Anabasis. Studia Classica et Orientalia, 2017)
This article deals with some issues concerning the ostentatious burials of the Lower Don region dating to the 1st century AD. Their exegesis in ethnic sense as markers of the migration of new Iranian-speaking tribes from Inner Asia to the West is still predominant in the Russian-speaking academic literature. This view is represented, for instance, in the newly published book by Leo Klein (2016). However, there are better evidenced approaches to the interpretation of rich nomadic burials in the steppes. Primarely, they could be considered as an evidence of cultural-political developments the North Pontic region.